(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The purpose of the authors in this study was to determine the theoretical and practical aspects of human capital development in the framework of forming the competitive economy. The conditions of the impact of human capital on economic development are being analyzed. The authors conclude that human capital has all the properties and show intensive development factors, but there are some problems with the precise measurement of its cost and performance. According to the authors, the integration of education, science and production, development of post-graduate education on the basis of modern achievements of science and technology are today one of the priority lists of the economic development.